Características médias da circulação atmosférica em eventos de neve no sul do Brasil - Mintegui, Jéssica Melo (2017)
In this work the mean behavior of atmosphere preceding and during snowfall events was investigated. Furthermore, anomalous fields correlated to snowfall events related to an atmospheric base state were quantified. To accomplish this task, a snowfall event sample was generated from weather reports provided by surface meteorological stations maintained by the Instituto Nacional de Meteorologia (INMET) and the Centro de Informações de Recursos Ambientais e Hidrológicos de Santa Catarina (Ciram), linked to the Empresa de Pesquisa Agropecuária e Extensão Rural de Santa Catarina (Epagri). The present study comprises the period between 1979 and 2015, where 196 snowfall events were found. To represent the atmospheric fields, ERA-Interim reanalysis data from the European Centre for Medium-Range Weather Forecasts (0:75_ _ 0:75_ grid spacing at 00 UTC and 12 UTC) were employed. Mean sea-level pressure, thickness between 1000 hPa - 500 hPa, 1000 hPa - 850 hPa, relative humidity, specific humidity and temperature at 850 hPa level, geopotential height and wind speed at 850 hPa, 500 hPa and 200 hPa levels were analyzed. Overall, snowfall occurrence in southern Brazil is associated with a transient baroclinic disturbance identified, mainly, by an anomalous dipole in the geopotential height and wind fields. The snowfall events take place after the displacement of a cold front over southern Brazil. On the days preceding the events, an anticyclone, which crosses the Andes Mountain Range from the Pacific Ocean, moves into southern South America. This anticyclone has a pronounced ridge that ensures equatorward flow, advecting cold air into southern Brazil. Because of the fast atmospheric cooling in southern Brazil, associated with cold advection, relative humidity does not exhibit decreases on the day before and on the first day of snowfall, even with a reduction in the atmospheric water vapor content.